Do intraspecific life history patterns follow interspecific predictions? A test using latitudinal variation in ringed seals. Issue 4 (13th June 2019) - Ferguson, Steven H.; Yurkowski, David J.; Young, Brent G.; Willing, Cornelia; Zhu, Xinhua; Muir, Derek C. G.; Fisk, Aaron T.; Thiemann, Gregory W.
Abstract: Mammals adapted to unpredictable and low‐energy environments often evolve a "bet‐hedging" life history strategy characterized by less costly reproductive outputs over a longer and slower‐growing life. In contrast, species adapted to more predictable (i.e., low variation) and higher energy environments may evolve greater fecundity over a shorter and faster‐growing life. We tested whether this known interspecific pattern also occurs within a species. We compared life history traits of the ringed seal ( Pusa hispida ) in the Canadian High Arctic to those closer to the southern limit of the species' circumpolar distribution. We found that northern seals grew slower than southern seals (Brody growth coefficient), achieved a greater asymptotic body weight (82 and 69 kg vs. 74 and 54 kg female and male, respectively), reached sexual maturity later (6.1 years vs. 4.5 years), had lower fecundity (1.8 years vs. 1.3 years interbirth interval), longer average lifespan (5 years vs. 3 years median age), and greater movements (1, 269 vs. 681 km). Mating systems also likely differed with northern seals showing morphological evidence of a promiscuous mating system with potential sperm competition as indicated by greater relative testes size. The northern region was also characterized by more unpredictable environmental timing of seasonal events, such as spring sea ice breakup. Life history variation between the intraspecific groups of seals appears to agree with interspecific patterns and provides a better understanding of how species' life history parameters shift in concert with environmental conditions. Abstract : The first study of an aquatic predator to find that life‐history and mating system patterns within a species range follow interspecific predictions. The results help to understand the mechanistic changes connecting environment and intraspecific patterns in life‐history. The photographer Jeff Higdon gave his permission to use the GTOC image.